WHY DONâT WE ADOPT PROFESSIONAL DEVELOPMENT SCHOOL FOR INDONESIAN FIELD EXPERIENCE PRACTICE? - Kusumaningrum, Widya Ratna (VISION, 2014)
ABSTRACT Popular known as PPL stands for Praktik Pengalaman Lapangan, the pre-service teacher education program in Indonesia is at critical condition, as it is seen from the pre-service teacherâs mastery content knowledge, inquiry, collaboration/ partnership, and accountability. By using a comparative study, I give direct comparison PPL to PDS. PDS or Professional Development School is a program facilitates the pre-service teacher candidates to have teaching experience and develop their professionalism. I try to uncover the principles of PPL and PDS and exemplify how these principles are implemented in practices. In this paper, I propose a new PPL model by evaluating the PPL practice, adopting PDS principles and restructuring toward PPL model in order to improve teaching quality in Indonesia. Keywords: pre-service teachers, teaching experience, profesionalism